If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(x + -3) + -1x + 2 + -2(x + 1) = 3(3 + x) + -9 Reorder the terms: 10(-3 + x) + -1x + 2 + -2(x + 1) = 3(3 + x) + -9 (-3 * 10 + x * 10) + -1x + 2 + -2(x + 1) = 3(3 + x) + -9 (-30 + 10x) + -1x + 2 + -2(x + 1) = 3(3 + x) + -9 Reorder the terms: -30 + 10x + -1x + 2 + -2(1 + x) = 3(3 + x) + -9 -30 + 10x + -1x + 2 + (1 * -2 + x * -2) = 3(3 + x) + -9 -30 + 10x + -1x + 2 + (-2 + -2x) = 3(3 + x) + -9 Reorder the terms: -30 + 2 + -2 + 10x + -1x + -2x = 3(3 + x) + -9 Combine like terms: -30 + 2 = -28 -28 + -2 + 10x + -1x + -2x = 3(3 + x) + -9 Combine like terms: -28 + -2 = -30 -30 + 10x + -1x + -2x = 3(3 + x) + -9 Combine like terms: 10x + -1x = 9x -30 + 9x + -2x = 3(3 + x) + -9 Combine like terms: 9x + -2x = 7x -30 + 7x = 3(3 + x) + -9 -30 + 7x = (3 * 3 + x * 3) + -9 -30 + 7x = (9 + 3x) + -9 Reorder the terms: -30 + 7x = 9 + -9 + 3x Combine like terms: 9 + -9 = 0 -30 + 7x = 0 + 3x -30 + 7x = 3x Solving -30 + 7x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -30 + 7x + -3x = 3x + -3x Combine like terms: 7x + -3x = 4x -30 + 4x = 3x + -3x Combine like terms: 3x + -3x = 0 -30 + 4x = 0 Add '30' to each side of the equation. -30 + 30 + 4x = 0 + 30 Combine like terms: -30 + 30 = 0 0 + 4x = 0 + 30 4x = 0 + 30 Combine like terms: 0 + 30 = 30 4x = 30 Divide each side by '4'. x = 7.5 Simplifying x = 7.5
| 2(3n+8)=16 | | 2(3n+8)=18 | | 64x2+(30/3) | | -2x^2+9x+7=0 | | 12-10x=84-24x | | 2(6n+8)=18 | | 2(6n+10)=18 | | x-7.1=-6.6 | | 2(6n+6)=18 | | 102x=1/100 | | 2(6n+2)=18 | | 1-r/4r/1+r/8r | | 2(6n+2)=20 | | 2(6n+8)=8 | | 2(6n+8)=14 | | 2(6n+7)=10 | | 2(6n+3)=12 | | -8x+4=-26x+1 | | 2(6n+2)=8 | | (5x-3)(x-9)=0 | | 2(6n+3)=8 | | 5y+9-y=10+3y+7 | | 11p+14=3p-64 | | 1/4z=-2 | | 1+4x=34+x+-34 | | 4m+117-3m=36 | | 2(5n+4)=12 | | 24/t+4/6/t | | 17y+12=-5 | | 2(4n+5)=10 | | 5c-4/7-3c+2/3 | | c^3-3c^2-40c=0 |